Fluoride Level and Water Quality in Ground Water Samples of Coastal Areas in Radhapuram Taluk of Tirunelveli District - Santhi, D. (Asian Journal of Chemistry, 2010)
The present work deals with the concentrations of fluoride and various parameters such as pH, electrical conductivity, total hardness, total alkalinity, chloride and salinity in Radhapuram taluk of Tirunelveli district. These parameters were recorded by means of collecting fifteen samples of drinking water from different parts of seven villages of this region. Fluoride in ground water is heterogeneously distributed and is in the range of 1.6–4.4 ppm, which is much above the permissible limits.